An examination of the interaction between climate, soil and leaf area index in a Quercus ilex ecosystem - Hoff, Corine; Rambal, Serge (Ann. For. Sci., 2003)
In Mediterranean-type ecosystems, water availability is one of the most significant variables that regulates whole plant leaf area. An equilibrium should exist between climate, soil and leaf area in such water-limited conditions. The aim of this study was to identify the relations between leaf area index (LAI), environment (climate, soil) and fluxes (water, carbon) in Mediterranean evergreen oak (Quercus ilex L.) ecosystems. To achieve this objective, 50-years simulations were performed using the FOREST-BGC model by varying LAI for a reference site and for different climates and soil water holding capacities (SWC). Transpiration, drought stress, net photosynthesis and canopy water use efficiency (WUE) were examined on a yearly basis for the last ten years of the simulation. Similar to other findings, our results show that LAI depends on site water availability, including both climate (precipitation, potential evapotranspiration) and soil factors (e.g. water storage capacity). Low SWC limit the development of the ecosystem. On high SWC soils, development is mainly limited by the climate. When LAI increases under constant SWC and climate conditions, the decrease in annual transpiration per unit of LAI is accompanied by an increase in drought stress. Equilibrium LAI maximizes carbon assimilation. For the reference site, the equilibrium LAI is close to the observed value, 3.25. The corresponding transpiration, assimilation and WUE are 375 mm, 1251 g C m -2 and 3.1 mmol CO 2 mol -1 H 2O, respectively. For the different sites, there is an hyperbolic decline of WUE with increasing SWC. This implies that production efficiency per unit leaf area is higher in most water-limited environments. Our study shows that a model such as FOREST-BGC allows inter-relations between water balance, carbon balance and drought stress to be taken into account to better understand ecosystem LAI.
Keywords: climate; evergreen oak; hydrological equilibrium; leaf area index; mediterranean-type ecosystem; Quercus ilex L.; soil factor; Water availability

The dehesa system of southern Spain and Portugal as a natural ecosystem mimic - Joffre, R; Rambal, S; Ratte, J P (Agroforestry Systems, 1999)
The dehesas of the southwestern Iberian Peninsula are ‘man-made’ ecosystems characterised by a savannah-like physiognomy. The trees are viewed as an integrated part of the system, and as a result are planted, managed, and regularly pruned. Palynological and historical evidence of the manipulation of initial ecosystems by man to obtain a savannah-like ecosystem is presented. The ecological functions of the tree are detailed using results obtained at two complementary scales. At the local scale, strong soil structural differences and functional differences in water budget and patterns of water use are observed under and outside the tree canopy. Using the concept of ecosystem mimicry, the two coexistent components of dehesas can be compared to two distant stages of a secondary succession characterised by very different behaviours. At the regional scale, evidence of relationships between tree density and mean annual precipitation over more than 5000 km2 suggests that the structure of these man-made agroecosystems have adjusted over the long-term and correspond to an optimal functional equilibrium based on the hydrological equilibrium hypothesis. Finally, the future of dehesas in the face of contemporary exogenous threats of economic and global environmental origin is discussed. 1. Introduction
Keywords: hydrological equilibrium; Mediterranean climate; optimality; Quercus ilex; Quercus suber; water balance

HOW TREE COVER INFLUENCES THE WATER-BALANCE OF MEDITERRANEAN RANGELANDS - Joffre, R; Rambal, S (ECOLOGY, 1993)
Dehesa ecosystems of the southwestern Iberian Peninsula are characterized as a savanna-like rangeland dominated by scattered mediterranean evergreen oak trees. We investigated whether isolated trees modify the water balance of this ecosystem and if so, what implications this finding might have on models that assume homogeneity of soil water resources. The water balance of the two ecological components of the dehesas-(1) the tree-grass component, and (2) the open areas between the tree canopies with unshaded grass vegetation-was studied for three consecutive years in three locations in the Sierra Norte de Sevilla region of Andalusia in southern Spain. In this region, annual rainfall was generally between 600 and 800 mm, and the summer drought lasted almost-equal-to 130 d. Soil water storage was measured with a neutron moisture gauge outside and under the tree canopy. Deep drainage between two consecutive census dates was calculated using field-measured drainage characteristics. Evapotranspiration (Ea) and surface runoff were computed from the water balance equation assuming that Ea is limited by Penman potential evapotranspiration. Monthly Ea by annual species in open areas was poorly correlated with rainfall levels in the autumn and was limited during the spring by availability of water in the top 40 cm of soil. During summer, monthly Ea by trees ranged from 30 to 50 mm. Mean annual Ea was 400 mm outside and 590 mm under the tree cover. In open areas, water yield (WY), defined as the sum of deep drainage and surface runoff, ranged from 65 to 100% of total Ea, whereas under the tree canopy WY was only 20 to 40% of the Ea. Under the tree canopy, when annual precipitation was < 570 mm, WY was negligible and all precipitation was lost by evapotranspiration. Outside the tree canopy, WY occurred as soon as annual precipitation exceeded 250 mm. Models of competition between trees and grass generally assume a spatial homogeneity of soil hydrodynamic properties. Our results, however, show that both soil water storage and evapotranspiration are greater for the tree-grass component. Consequently, these models must account for this spatial variability in water resources according to species.
Keywords: DEEP DRAINAGE; Dehesa; Evapotranspiration; Grasses; hydrological equilibrium; MEDITERRANEAN OAK WOODLANDS; Quercus ilex; Quercus-suber; surface runoff; Trees; water balance